If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 45 = -9(y + 5) Reorder the terms: 45 + 6y = -9(y + 5) Reorder the terms: 45 + 6y = -9(5 + y) 45 + 6y = (5 * -9 + y * -9) 45 + 6y = (-45 + -9y) Solving 45 + 6y = -45 + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. 45 + 6y + 9y = -45 + -9y + 9y Combine like terms: 6y + 9y = 15y 45 + 15y = -45 + -9y + 9y Combine like terms: -9y + 9y = 0 45 + 15y = -45 + 0 45 + 15y = -45 Add '-45' to each side of the equation. 45 + -45 + 15y = -45 + -45 Combine like terms: 45 + -45 = 0 0 + 15y = -45 + -45 15y = -45 + -45 Combine like terms: -45 + -45 = -90 15y = -90 Divide each side by '15'. y = -6 Simplifying y = -6
| Y=x^4+2x^3+4x^2+8x+1 | | 9/15/2/4= | | 2-b-4a+2ab=0 | | 4w+30=-2(w+6) | | a=3b+4 | | 5x-5=3(x-1) | | 2x^2+lax+2=0 | | H=16t^2+4t | | a=5b+1 | | 6331/x=0.13 | | 1316=x*(19+x) | | -9+20=19(15)-4-18(15) | | y=4x^3+6x^2+8x+8 | | 90+(3x)+(2x+20)=180 | | 8-c=-14 | | 6[x-2(3x+7)]=4x-5 | | 7x+0.4=21.4 | | Z^2-(3-2i)Z+37+9i=0 | | 7h+26=34 | | 3x-3=7x+17 | | 23-x=24 | | 26=7r-9 | | 17=-5(4x+2)+21x | | 7h-26=34 | | t+3-2=9 | | -2a+33+7a=3a-9a | | 2x+38+4x=180 | | a+5+1=13 | | 12x+27=6x+165 | | 12x+27=.6x+165 | | 3(5-3x)-8=88 | | 3x-3=9-3x |